The Difference of Lured Rat Number between Uncombined and Combined Bait Trapping (Unnes Journal of Public Health, 2020)
Abstract Live traps usually can only trap rats in the first day of trapping because the bait become not luring anymore after the first day of trapping. The purpose of this study was to determine the differences in lured rats number between uncombined bait trapping and combined bait trapping. This is a quasi-experimental study with a post-test only non-equivalent control group design. Each house has 5 traps setup with 6 replications. One trap was set with combined bait types (rice, anchovy, tofu and roasted coconut) and four other traps set with separated uncombined bait types; (1) rice, (2) anchovy, (3) tofu, (4) roasted coconut. The instruments used were house screening sheets, traps and observation sheets. The data obtained were tested with the Mann-Whitney test. The results showed that there were not significant differences in trapped rats number between combined bait and uncombined rice bait (p=0.748), between combined bait and uncombined anchovy bait (p=0.355), between combined bait and uncombined tofu bait (p=1.000), and also between combined bait and uncombined roasted coconut bait (p=0.734). Uncombined anchovies bait trapped rats most. Combined bait and uncombined anchovy bait were most consistent in trapping rats.